2009
DOI: 10.2147/ccid.s4057
|View full text |Cite
|
Sign up to set email alerts
|

Fixed drug eruption induced by atenolol

Abstract: Fixed drug eruption (FDE) is characterized by recurrent well-defined lesions in the same location each time the responsible drug is taken. We report here a case of multiple FDE induced by atenolol in a 48-year-old woman confirmed by positive patch test in previously affected sites. Beta-blockers-induced FDE are very rare. Only two cases had been reported in the literature. To the best of our knowledge, this is the first case reported of atenolol-induced FDE confirmed by a positive patch test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Limited research has investigated the frequency of FDEs associated with chlorthalidone. Some of the antihypertensives that have been described are diltiazem, enalapril, amlodipine, propranolol, atenolol, bisoprolol, nifedipine, hydralazine, and indapamide [5,6,7]. Some studies showed a trend toward male predominance, although female predominance has also been reported [8].…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has investigated the frequency of FDEs associated with chlorthalidone. Some of the antihypertensives that have been described are diltiazem, enalapril, amlodipine, propranolol, atenolol, bisoprolol, nifedipine, hydralazine, and indapamide [5,6,7]. Some studies showed a trend toward male predominance, although female predominance has also been reported [8].…”
Section: Discussionmentioning
confidence: 99%
“…Herz-Kreislauf-Medikamente  Betablocker: Atenolol [93], Bisoprolol [94], Propranolol [95] 1999 Thailand [96] ET 1 Sonstige 1 Hx 1 < 5…”
Section: Antibakterielle Wirkstoffeunclassified